Time Gone, We Stay - Connecting to the Balinghou Collective Memory Through Narrative and Zine - Zhou, Xiaoying (Zoey) (Auckland University of Technology, 2020)
The Chinese post-80s generation are known in China as ‘Balinghou’. The loneliness brought by the ‘one-child policy’ led to a selfish and independent Balinghou. Their exam-oriented education focussed on theoretical learning, resulting in a lack of practical abilities. The Balinghou struggle under fierce competition for employment, which exacerbates the financial pressure and the huge of the duty of bringing up both children and supporting parents in a 421-family structure. The recent resurgence of interest in childhood comics, toys and snacks reflects this generation attempts to reconnect with the carefree days of their youth. Behind this wave of nostalgia is a desire to retreat from the pressures of their current, adult lives. My research project uses visual storytelling to unpack my opinions and interpret key issues for Balinghou. I have explored the concept of ‘reflective nostalgia’ as a new perspective that offers a critical way of thinking about generational identity and culture, as influenced by societal development. I have used the Zine format as a way to combine personal stories and social history. Zines were an effective way for me to advocate self-voice and create emotional resonance with my Balinghou readers. This project hopes to encourage Balinghou readers to gain strength through reflecting on their past so that they might face the pressure of their current reality more calmly. The study of narratology prompted me to examine how to construct a narrative and build multiple ways to communicate with my readers. I established six narrative strategies to support me in a bold exploration of visual storytelling by applying different narrative strategies to content. Auto-ethnographic research encouraged me to delve into my personal experiences that related to my six selected Balinghou themes. Reflecting on the past through writing and drawing helped me to unpack my feelings, which in turn helped my design work more convincingly connect to the Balinghou collective memory. Action research drove me to improve my design practice and visual storytelling constantly. It guided me to employ new knowledge in my practice through an iterative design process. The design outcome of my research consists of six Zines, with each Zine unpacking one of six themes, based on key aspects of the Balinghou life experience. My zines weave together text, illustrations and graphics into the narrative to form a coherent design. There is also a mix of Chinese and English language content to connect to both Balinghou and non-Chinese readers. The collective narratives and visual storytelling in my Zines aim to create an emotional resonance with my Balinghou readers.
Keywords: Zine; Chinese Balinghou; Visual narrative; Reflective nostalgia; Auto-ethnography; Narratology; Collective memory; Generation experience